Plant Variety Protection Regime in Relation to Relevant International Obligations: Implications for Smallholder Farmers in Kenya. (March 2015) - Munyi, Peter
Abstract : Together with other laws affecting agriculture, Kenya's plant varieties protection legislation was radically amended in 2012. The amendments were mainly driven by the quest to comply with international obligations, principally the 1991 UPOV Convention. However, the country is also a contracting party to other international treaties affecting seeds such as the International Treaty on Plant Genetic Resources for Food and Agriculture and the WTO Agreement on Trade Related Aspects of Intellectual Property Rights. Moreover, the national Constitution obligates statutory recognition and protection of the ownership of indigenous seeds and plant varieties, their genetic and diverse characteristics, and their use by the communities of Kenya. The obligations deriving from all these international agreements must be fulfilled against a backdrop of farming systems that are predominantly smallholder farmer‐based. This article discusses how the amendments in the new Kenya plant variety protection law depart from the former legal regime and analyzes whether the current regime is compliant with international obligations, and the implications for smallholder farmers.